2020
DOI: 10.1371/journal.ppat.1008485
|View full text |Cite
|
Sign up to set email alerts
|

System-wide biochemical analysis reveals ozonide antimalarials initially act by disrupting Plasmodium falciparum haemoglobin digestion

Abstract: Ozonide antimalarials, OZ277 (arterolane) and OZ439 (artefenomel), are synthetic peroxide-based antimalarials with potent activity against the deadliest malaria parasite, Plasmodium falciparum. Here we used a "multi-omics" workflow, in combination with activity-based protein profiling (ABPP), to demonstrate that peroxide antimalarials initially target the haemoglobin (Hb) digestion pathway to kill malaria parasites. Time-dependent metabolomic profiling of ozonide-treated P. falciparum infected red blood cells … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 105 publications
(197 reference statements)
7
37
0
Order By: Relevance
“…Pre-treatment with E64d and co-incubation with increasing concentrations of OZ03 inhibited OZ727 binding to food vacuole proteins (Figure S2), confirming that these targets are important for peroxide activity. These findings are consistent with peroxides initially acting by disrupting parasite haemoglobin digestion 32 , an essential process that occurs within the parasite food vacuole. GO analysis further revealed that peroxide protein targets were involved in numerous essential biological processes of the parasite (Figure 3 and Supplementary Data 3).…”
Section: Identification Of Protein Targets Of Peroxide Antimalarialssupporting
confidence: 86%
See 1 more Smart Citation
“…Pre-treatment with E64d and co-incubation with increasing concentrations of OZ03 inhibited OZ727 binding to food vacuole proteins (Figure S2), confirming that these targets are important for peroxide activity. These findings are consistent with peroxides initially acting by disrupting parasite haemoglobin digestion 32 , an essential process that occurs within the parasite food vacuole. GO analysis further revealed that peroxide protein targets were involved in numerous essential biological processes of the parasite (Figure 3 and Supplementary Data 3).…”
Section: Identification Of Protein Targets Of Peroxide Antimalarialssupporting
confidence: 86%
“…This process results in cleavage of the peroxide bond and generation of carbon-centered radicals 11,16 that alkylate haem [17][18] and proteins [19][20][21][22][23][24][25][26] and induce widespread oxidative stress [27][28][29][30][31] . Death of the parasite likely results from disruption to multiple vital processes, including haemoglobin degradation in the food vacuole 32 . Concerningly, parasites with decreased sensitivity to artemisinins have emerged in the Greater Mekong Subregion 33 , and more recently in eastern India 34 , Africa 35 and Papua New Guinea 36 .…”
Section: Introductionmentioning
confidence: 99%
“…The current portfolio contains a number of promising drug candidates like arterolane (OZ277, Figure 13 , 40 ), artefenomel (OZ439, 41 ) and ferroquine ( 30 ) [ 73 , 74 ]. Artefenomel ( 40 ) and arterolane ( 39 ), like the artemisinins, contain a 1,2,4-trioxane ring and has the same mechanism [ 87 ]. The advantages of these drugs are longer half-lives in the body, 4 hours for arterolane [ 87 ] and 23 hours for artefenomel [ 73 , 87 ] in contrast to the 1 hour half-life of artemisinins.…”
Section: Malariamentioning
confidence: 99%
“…Artefenomel ( 40 ) and arterolane ( 39 ), like the artemisinins, contain a 1,2,4-trioxane ring and has the same mechanism [ 87 ]. The advantages of these drugs are longer half-lives in the body, 4 hours for arterolane [ 87 ] and 23 hours for artefenomel [ 73 , 87 ] in contrast to the 1 hour half-life of artemisinins. Long time exposure to the drugs is expected to make Kelch13 mutated parasites more sensitive [ 73 ].…”
Section: Malariamentioning
confidence: 99%
See 1 more Smart Citation